Accuracy of One-Piece vs. Segmented Three-Dimensional Printed Transfer Trays for Indirect Bracket Placement - Bayan Alyammahi; Amar Hassan Khamis; Ahmed Ghoneima (MDPI AG, 2024)
Objective: To assess the accuracy of three-dimensional (3D) printed one-piece vs. multiple segmented transfer trays for indirect bonding techniques in moderate and severe crowding cases. Methods: Eighty digital maxillary dental models were produced by an extraoral scanner. 3D-printed one-piece and segmented trays were virtually designed utilizing Maestro 3D Ortho Studio® v4 and printed using a NextDent printer. The sample was classified into two groups: Group 1 (moderate crowding) included 40 digital models with a space deficiency of 6-7 mm, and Group 2 (severe crowding) included 40 digital models with a space deficiency of 10 mm. Ortho classic brackets were then placed into the 3D printed models with the aid of the transfer trays, and the models with the final bracket positioning were scanned using iTero scanner. Four measurements were selected on each tooth to perform the analysis. Mann-Whitney and Kruskal-Wallis tests were used for comparisons. A p-value of ≤ 0.05 was considered statistically significant. Results: In the moderate crowding group, statistically significant differences were detected between the one-piece, segmented, and control groups for three measurements (p < 0.001), while the rest of the measurements showed no significant differences (p > 0.05). In the severe crowding group, no significant differences were detected for any of the measurements. Conclusions: One-piece and segmented 3D-printed transfer trays are considered accurate tools for indirect bonding in moderate and severe malocclusion cases. The severity of crowding did not affect the accuracy of bracket transfer in indirect bonding.